2014
DOI: 10.1007/s11099-014-0011-3
|View full text |Cite
|
Sign up to set email alerts
|

A modified nonrectangular hyperbola equation for photosynthetic light-response curves of leaves with different nitrogen status

Abstract: Chlorophyll index and leaf nitrogen status (SPAD value) was incorporated into the nonrectangular hyperbola (NRH) equation for photosynthetic light-response (PLR) curve to establish a modified NRH equation to overcome the parameter variation. Ten PLR curves measured on rice leaves with different SPAD values were collected from pot experiments with different nitrogen (N) dosages. The coefficients of initial slope of the PLR curve and the maximum net photosynthetic rate in NRH equation increased linearly with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 43 publications
3
29
1
Order By: Relevance
“…The Rd significantly 6 irradiance were able to maximize photosynthesis if CMR values were higher than 53 (about 2% of total N). The increase in maximum photosynthetic rate and light saturation point with higher CMR readings or N availability found in this study were also described by Lin et al (2013) in oats and by Xu et al (2014) in rice. The better relationship obtained between CMR readings and light-saturated photosynthesis with measurements on July 27th and August 17 th 2011 compared to the earlier instantaneous gas exchange measurements on June 23 rd and July 7 th can indicate that leaf photosynthesis became more limited by N availability later in the growing season.…”
Section: Discussionsupporting
confidence: 83%
“…The Rd significantly 6 irradiance were able to maximize photosynthesis if CMR values were higher than 53 (about 2% of total N). The increase in maximum photosynthetic rate and light saturation point with higher CMR readings or N availability found in this study were also described by Lin et al (2013) in oats and by Xu et al (2014) in rice. The better relationship obtained between CMR readings and light-saturated photosynthesis with measurements on July 27th and August 17 th 2011 compared to the earlier instantaneous gas exchange measurements on June 23 rd and July 7 th can indicate that leaf photosynthesis became more limited by N availability later in the growing season.…”
Section: Discussionsupporting
confidence: 83%
“…The A max , AQY and R d are not only important photosynthetic indicators but also core parameters for determining the shape of the PLR curve (Equation (2)). Thus, many studies have linked leaf traits [11,16,32,91] or environmental conditions [20,29] in the PLR models based on their correlations with the A max , AQY and R d to resolve the problem of parameter variation among different species or environments. In this study, we comprehensively considered the influence of spatial position, leaf traits and environmental conditions on leaf photosynthesis and then linked the RDINC, LMA and VPD in the PLR model to extend the PLR model from a single leaf to the whole crown and render the model sufficiently flexible to be applied in different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that incorrect simulations usually occur when modeling long-term carbon uptake if the spatial and seasonal variations in photosynthesis [46,[92][93][94][95] or leaf traits [96,97] are neglected. Some scientists have successfully incorporated leaf traits [11,16,29,32,91] and environmental conditions [20,29] into the PLR model to extend the model from a single leaf to a larger scale. However, these models are limited in their application because they only describe the response of the A n to PAR in different conditions and do not describe the dynamic simulation of the A n .…”
Section: Discussionmentioning
confidence: 99%
“…The photosynthetic light response curve, which describes the relationship between leaf photosynthetic rate and light levels (PPFD), helps to characterize plant photosynthetic capacity [15,23]. Here, we used this method to estimate carbon assimilation variables across different seasons and found that the light response curve was saturated at a lower PPFD during the dry season.…”
Section: Discussionmentioning
confidence: 99%